Enabling the new economic actor: data protection, the digital economy, and the Databox. Issue 6 (November 2016) - Crabtree, Andy; Lodge, Tom; Colley, James; Greenhalgh, Chris; Mortier, Richard; Haddadi, Hamed
Abstract This paper offers a sociological perspective on data protection regulation and its relevance to design. From this perspective, proposed regulation in Europe and the USA seeks to create a new economic actor—the consumer as personal data trader—through new legal frameworks that shift the locus of agency and control in data processing towards the individual consumer or "data subject". The sociological perspective on proposed data regulation recognises the reflexive relationship between law and the social order, and the commensurate needs to balance the demand for compliance with the design of computational tools that enable this new economic actor. We present the Databox model as a means of providing data protectionand allowing the individual to exploit personal data to become an active player in the emerging data economy.